Implementing the Make a Match Model to Improve Third-Grade Students' Speaking Skills: An Action Research Study - Septiana Nur; Muhammad Aqil; Surahman Wilade; Rizal Rizal; Sisriawan Lapasere (Journal of Innovation and Research in Primary Education, 2026)
Speaking skills remain inadequately developed in Indonesian elementary education, with students exhibiting passive participation, low confidence, and limited verbal interaction opportunities. This study investigated the effectiveness of the Make a Match cooperative learning model in enhancing third-grade students' speaking competencies through systematic classroom intervention. Employing classroom action research methodology across two iterative cycles at SD Inpres 3 Tondo, this study involved 28 third-grade students and one teacher during the 2025 academic year. Data were collected through structured observations, learning outcome assessments, interviews, and documentation, with analysis integrating quantitative descriptive statistics and qualitative thematic interpretation to evaluate teacher pedagogical quality, student engagement patterns, and speaking achievement outcomes. Substantial improvements were documented across all measured dimensions. Teacher pedagogical quality increased from 61.11% in Cycle I to 94.44% in Cycle II, while student engagement rose from 44.44% to 94.44%. Most significantly, academic achievement rates improved dramatically from 41.67% to 83.33% of students meeting the minimum completion criterion, representing a 41.66 percentage point gain. Findings validate that Make a Match cooperative learning, when implemented with skilled facilitation including enhanced supervision, motivational strategies, and explicit procedural guidance, effectively transforms passive learners into confident communicators. This research contributes empirical evidence demonstrating that speaking skill development requires integrated attention to pedagogical structures, teacher quality, and student psychological support within cooperative learning frameworks.